Organizational and legal aspects of digitalization of public authorities in Ukraine - Pendiura, Maksym; Lukashenko, Alona; Lapka, Oksana; Kryvenko, Valeriia; Tykhomyrov, Denys; Savelieva, Inna (Revista Brasileira de Direito, 2023)
The scientific work is dedicated to highlighting the organizational and legal aspects of digitalization of state authorities in Ukraine. It is noted that these public relations in the conditions of global digital transformation structurally consist of relations arising in connection with the implementation of executive and administrative activities of state authorities, the provision of electronic administrative services and the provision of rights and freedoms of citizens through the use of information and communication technologies. It is indicated that the key imperatives of state management of digital development are end-to-end digitalization, promotion of the development of the information society, stimulation of international digital cooperation, provision of information and communication technologies to all segments of the population, formation of digital skills, provision of digital security and protection of digital rights and freedoms of citizens. Prospective directions for strengthening the digital capacity of state authorities and improving their communication capabilities in Ukraine were identified, and the importance of the appropriate modern legal basis for the system of digitization of state authorities and state administrative services was emphasized.